Matrix structural analysis - Felton, Lewis P. (John Wiley & Son, 1997)
The field of structural analysis has experienced profound change in the past three decades. This book presents a rigorous, concise development of the concepts of modern matrix structural analysis with emphasis on techniques and methods which are the basis for the Finite Element Method. The material is presented in a traditional manner. Basic analytical tools set the groundwork for understanding more complex concepts. Meaningful examples which illustrate the underlying theories and procedures are provided throughout the text, presented in a step-by-step format to promote understanding.